2010
DOI: 10.1179/joc.2010.22.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Versus Fosfomycin Tromethanol in the Treatment of Extended-Spectrum Beta-Lactamase-ProducingEscherichia Coli-Related Complicated Lower Urinary Tract Infection

Abstract: The aim of this observational prospective study was to compare the effect of fosfomycin tromethanol (FT) and carbapenems (meropenem or imipenem cilastatin) in the treatment of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli-related complicated lower urinary tract infection (CLUTI). Inclusion criteria were: patients who were aged >18 yr with dysuria or problems with frequency or urgency in passing urine; those with >20 leukocytes/mm³ in urine microscopy and culture-proven ESBL-producing carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 8 publications
3
63
0
4
Order By: Relevance
“…In a small observational study of patients with complicated lower UTI due to ESBL-producing E. coli, oral fosfomycin trometamol was compared with carbapenem treatment. Clinical and microbiological success with fosfomycin and carbapenems was not significantly different (77.8% versus 95% and 59.3% versus 80%, respectively; P Ͼ 0.05) (229). In addition, a discordance between in vitro susceptibility to fosfomycin and microbiological effectiveness was observed in patients with P. aeruginosa (75% versus 38%) and CR K. pneumoniae UTIs (92% versus 46%) (230).…”
Section: Urinary Tract Infectionsmentioning
confidence: 87%
“…In a small observational study of patients with complicated lower UTI due to ESBL-producing E. coli, oral fosfomycin trometamol was compared with carbapenem treatment. Clinical and microbiological success with fosfomycin and carbapenems was not significantly different (77.8% versus 95% and 59.3% versus 80%, respectively; P Ͼ 0.05) (229). In addition, a discordance between in vitro susceptibility to fosfomycin and microbiological effectiveness was observed in patients with P. aeruginosa (75% versus 38%) and CR K. pneumoniae UTIs (92% versus 46%) (230).…”
Section: Urinary Tract Infectionsmentioning
confidence: 87%
“…In European countries similar rates have been reported. [13] Şenol et al [19] compared fosfomycin, and carbapenem in the treatment of complicated lower UTIs caused by E. coli, and despite comparable clinical, and microbiological success rates, the authors reported favourable cost-effectiveness with fosfomycin treatment. Fosfomycin appears to be an effective alternative in the current treatment of community-acquired urinary system infections thanks to ease of single dose applications, better patient compliance, lower complication rates, and its safe use in children, and pregnants.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently it retains good in vitro activity against ESBL-producing E. coli and K. pneumoniae [de Cueto et al 2006;Maraki et al 2009;Falagas et al 2010a]. Observational studies have shown that fosfomycin is effective for the treatment of lower UTIs due to ESBL-producing Enterobacteriaceae Senol et al 2010] and is our preferred therapy for such infections. There is very limited experience in the use of intravenous fosfomycin for invasive infections.…”
Section: Other Antimicrobialsmentioning
confidence: 99%